Relationship between MAN2B1 genotype/subcellular localization subgroups, antidrug antibody detection, and long‐term velmanase alfa treatment outcomes in patients with alpha‐mannosidosis - Borgwardt, Line Gutte; Ceravolo, Ferdinando; Zardi, Giulia; Ballabeni, Andrea; Lund, Allan Meldgaard (JIMD reports, 2023)
Alpha‐mannosidosis (AM), an autosomal recessive disorder caused by pathogenic biallelic variants in the MAN2B1 gene, leads to lysosomal alpha‐mannosidase deficiency and accumulation of mannose‐rich oligosaccharides. Velmanase alfa (VA), a recombinant human lysosomal alpha‐mannosidase, is the first enzyme replacement therapy for non‐neurological symptoms of AM. Previously, a potential relationship was identified between three MAN2B1 genotype/subcellular localization subgroups (G1, G2, and G3) and AM disease severity. In VA‐treated patients with AM, it is unknown if a relationship exists between MAN2B1 genotype/subcellular localization subgroups, antidrug antibodies (ADAs), and infusion‐related reactions (IRRs). This pooled analysis evaluated data from 33 VA‐treated patients with AM to investigate this relationship. Overall, 10 patients were positive for ADAs, 4 of whom had treatment‐emergent ADAs (G1: 3/7 [43%]; G2: 1/17 [6%]; G3: 0/9). Treatment‐emergent ADA‐positive patients with relatively high titers (n = 2; G1: 1012 U/ml and G2: 440 U/ml) experienced mild/moderate IRRs that were well‐managed; patients with lower titers (n = 2) experienced no IRRs. Overall, changes from baseline in serum oligosaccharides and immunoglobulin G levels did not vary between ADA‐positive and ADA‐negative patients, suggesting a similar effect of VA treatment regardless of ADA status in most patients. Clinical outcomes (3MSCT and 6MWT) were also similar in most patients regardless of ADA status. While further studies are needed, these data suggest a relationship between MAN2B1 genotype/subcellular localization subgroups and ADA development, with G1 and G2 subgroups more likely to develop ADAs and IRRs. Regardless, this study suggests that ADAs have limited effect on the clinical impact of VA in most patients with AM.